THE INFLUENCE OF SOCIAL MEDIA ON ADOLESCENT SEXUAL EXPLORATION AND SEXUAL BEHAVIOR: SCOPING REVIEW - Ermiati, Ermiati (Journal of Maternity Care and Reproductive Health, 2025)
Adolescents are a vulnerable group to the influence of social media, particularly in sexual exploration and behavior. This study aims to examine the literature on the influence of social media on adolescent sexual behavior through a scoping review approach. A literature search was conducted across six databases using keywords related to "adolescents OR teenagers" AND "social media use OR social media" AND "sexual behavior OR sexual activity OR online pornography" covering the years 2020-2025, with full text articles focusing on the influence of social media on adolescent sexual exploration and sexual behavior. Of the 8,443 articles found, 15 met the inclusion criteria. The study found that social media is associated with accelerated sexual development, exposure to pornography, and risky sexual behavior. Future research is recommended to focus on comprehensive sex education and digital media monitoring by families, schools, and health professionals to minimize negative impacts on adolescents.Keywords: Adolescents, social media, sexual behavior, pornography